Controlling for P‐value inflation in allele frequency change in experimental evolution and artificial selection experiments. (25th November 2016) - Kemppainen, Petri; Rønning, Bernt; Kvalnes, Thomas; Hagen, Ingerid J.; Ringsby, Thor Harald; Billing, Anna M.; Pärn, Henrik; Lien, Sigbjørn; Husby, Arild; Sæther, Bernt‐Erik; Jensen, Henrik
Abstract: Experimental evolution studies can be used to explore genomic response to artificial and natural selection. In such studies, loci that display larger allele frequency change than expected by genetic drift alone are assumed to be directly or indirectly associated with traits under selection. However, such studies report surprisingly many loci under selection, suggesting that current tests for allele frequency change may be subject to P ‐value inflation and hence be anticonservative. One factor known from genomewide association (GWA) studies to cause P ‐value inflation is population stratification, such as relatedness among individuals. Here, we suggest that by treating presence of an individual in a population after selection as a binary response variable, existing GWA methods can be used to account for relatedness when estimating allele frequency change. We show that accounting for relatedness like this effectively reduces false‐positives in tests for allele frequency change in simulated data with varying levels of population structure. However, once relatedness has been accounted for, the power to detect causal loci under selection is low. Finally, we demonstrate the presence of P ‐value inflation in allele frequency change in empirical data spanning multiple generations from an artificial selection experiment on tarsus length in two free‐living populations of house sparrow and correct for this using genomic control. Our results indicate that since allele frequencies in large parts of the genome may change when selection acts on a heritable trait, such selection is likely to have considerable and immediate consequences for the eco‐evolutionary dynamics of the affected populations.